The Short-time Effects of US News on the GBP/USD - Xu, Yaofei (2013)
This paper examines the relationship between 23 kinds of macroeconomic news and the return of foreign exchange rate in a short time, by using the high frequency transaction data on the spot exchange rate, GBP/USD. Among the 23 kinds of macroeconomic news, all kinds of macroeconomic news are significant at least in one of the all regressions. The price development in the first minute after the news released is analyzed, by using the data of 5 seconds interval and Weighted Least Squares to adjust heteroscedasticity. From the results of the regressions, the surprises of the most American macroeconomic news are proved to be ones of the driving forces behind the price developments of foreign exchange rate, GBP/USD, in the period from 2008 to 2012. In particular, the effects of the most macroeconomic news are reflected in the price development in the first minute after the news released, some of which have continuous effects in 1 minute. Moreover, during the first one minute, the coefficients of same news always change their signals in different intervals, because of the price overreaction and underreaction. Price reaction to news under high uncertainty and low uncertainty economic condition are compared. The news effects under expansion and depression economic condition are also discussed to show the price reaction to news under different circumstances.